Impact of COVID-19 on the clinical course of nephrotic syndrome in children: a single-center study - Min Ji Park; Jung Kwan Eun; Hee Sun Baek; Min Hyun Cho (Korean Society of Pediatric Nephrology, 2022)
Purpose Children with nephrotic syndrome may experience disease relapse or aggravation triggered by various viral infections. Limited studies on the clinical implications of the coronavirus disease 2019 (COVID-19) pandemic in children with nephrotic syndrome have been published worldwide. Therefore, this study aimed to investigate the effects of COVID-19 on the clinical course of nephrotic syndrome in children. Methods The medical records of 59 patients with idiopathic nephrotic syndrome who visited our hospital between February and June 2022 were retrospectively analyzed. Results Twenty of the total 59 patients with nephrotic syndrome were diagnosed with COVID-19 during the study period. The mean age at the time of the diagnosis of nephrotic syndrome and COVID-19 in all 20 patients was 4.6±3.5 and 8.9±3.9 years, respectively. Three patients (15%) were diagnosed with nephrotic syndrome relapse during COVID-19 and the relapse rate was similar to them without COVID-19 (20.5%, 8/39 patients). At the time of the COVID-19 diagnosis, fever (85%) and cough (40%) were the most common symptoms. After the diagnosis of COVID-19, all patients showed improvement with symptomatic treatment, including antipyretic analgesics and cold medicine. None of the critical patients required hospitalization or oral antiviral medications. Conclusions Despite the use of immunosuppressants, the clinical manifestations of COVID-19 in children with nephrotic syndrome were not severe and are expected to be similar to that in the general population. The relapse rate of nephrotic syndrome in children with COVID-19 was also not different from them without COVID-19.